Psychometric properties of Older Adults’ Entomophobia and Arachnophobia Scale (OAEAS): validating, cutoff points, IRT analysis, and its measurement invariance in Iranian version - Nasrabadi, Mahsa; Kashfi, Seyyed Mansour; Soltani, Aboozar; Ahmad, Siti Anom; Asadollahi, Abdolrahim (Wiley, 2024)
Objectives: Experiencing the fear of insects or other arthropods is more challenging for older adults than encountering insects themselves. The aim of this study is to measure this feeling in the Older Adults’ Entomophobia and Arachnophobia Scale (OAEAS) in the aging community of Iran. Materials and Methods: In a psychometric study, translation and validation of OAEAS (short version) have been done among a sample of 450 Persian-speaking older participants with mean score of years old 70.2 (SD = 8.3) (female = 61.4% and male = 38.6%). In the midyear of 2021, psychometric features of the OAEAS and its cutoff points for measuring fear of insects or other arthropods were investigated among Iranian older population. Using EFA and CFA, the extracted models, that is, PCA, GLS, and ML and also, test-retest reliability, ROC analysis, and convergent validity were also assessed. The polytomous Rasch model for all items has been prepared alongside extracted marginal maximum likelihood estimation (MMLE) and PCM model. Results: About 55.9% were married, 34.4% lived alone, and 65.6% did not live alone. Approximately 89.5% of the participants experienced insect bites in childhood, and 60% did not have pets at home. A total of 28.2% of the participants reported fear of flying insects or other arthropods, while 21.8% feared nonflying arthropods. Using EFA and CFA, it was indicated to internal consistency, accuracy, structural reliability, and convergent validity under 2 factors named entomophobia and entomophilia with eigenvalues close to once. The fit indices (mean indices ≥ 0.8) were the best for the 2-factor model with RMSEA = 0.04 (p ≤ 0.01). In the final analysis of the IRT method, two items (16 and 20) were removed from the OAEAS. The results of ROC analysis showed that the OAEAS has sufficient diagnostic validity to classify different groups. Discussion: The new version of OAEAS 18-items is a valid and reliable tool for assessing fear of insects or other arthropods in Iranian community-dwelling older adults. The possible uses and limitations of the Iranian version of the scale were also discussed.